Physiological Value of Heart Rate, Respiration and Rectal Temperature of Wild-Captive Dugong (Dugong dugon)–A Case Study in Lingayan Island - Aryani Sismin Satyaningtijas; Agik Suprayogi; Ardiansyah Nurdin; Huda S. Darusman (HAYATI Journal of Biosciences, 2019)
This study aims to obtain the physiological value of dugongs that live in natural habitats (in-situ) as protected wildlife, namely on the coast of Lingayan Island, Toli-Toli Regency. Wild dugongs caught on the beach were put into a net cage. After 14 days of living in a beach cage, measurements of heart rate, respiration, and body temperature were measured using non-invasive methods. This study showed that the value of heart rate, respiration, and body temperature were measured (80.00±17.32) beats/minutes, (17.33±6.80) inspiration/minute, and (32.75±0.07)°C. This physiological value is higher when compared to dugongs that live in captivity, this is likely due to the process of homeostasis through physiological adaptation mechanisms. The physiological value of the dugong is very important for the advancement of dugong animal health science and technology. Besides this finding can be a medical reference that is very useful for veterinarians in the diagnostic and therapeutic process.